Financial Crime and Early Criminology. The ambiguity of a concept forged in the eighteenth century - RUGGIERO, VINCENZO (Kriminologijos studijos, 2015)
This paper focuses on the contribution of early criminologists (particularly Beccaria and Bentham) to the analysis of the particular forms of crime of the powerful occurring in the financial arena. After a brief review of the contemporary criminological literature on financial crime, it provides, first, an account of some financial crises that occurred during the seventeenth and eighteenth centuries. Second, it searches within the writings of classical criminologists such as Beccaria and Bentham for definitions and clarifications as to what was regarded at the time as financial delinquency. Finally, in a concluding discussion, it highlights differences and similarities between past and current interpretations, all to a degree reflecting the ambiguous nature of this type of delinquency.
Keywords: Financial crime; crashes; crazes; fraud; bankers